y=-2xao quadrado+8x-6
zuccat:
a segunda equaçao por favor
Soluções para a tarefa
Respondido por
8
Y=-2x²+8x-6=0 (-1)
Y= 2x²-8x+6=0
a = 2
b = -8
c = 6
Δ = B²-4ac
Δ = -8² - 4·2·6
Δ = 64 - 48
Δ = 16
y = b² +- √Δ ÷ 2a
y = -8 +- √16 ÷ 2·2
y = -8 +- 4 ÷ 4
y' = - 8 - 4 ÷ 4
y' = -16 ÷ 4
y' = - 4
y" = - 8 + 4 ÷ 4
y" = -4 ÷ 4
y" = -1
S={-4 e -1}
Y= 2x²-8x+6=0
a = 2
b = -8
c = 6
Δ = B²-4ac
Δ = -8² - 4·2·6
Δ = 64 - 48
Δ = 16
y = b² +- √Δ ÷ 2a
y = -8 +- √16 ÷ 2·2
y = -8 +- 4 ÷ 4
y' = - 8 - 4 ÷ 4
y' = -16 ÷ 4
y' = - 4
y" = - 8 + 4 ÷ 4
y" = -4 ÷ 4
y" = -1
S={-4 e -1}
Perguntas interessantes
História,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás
Psicologia,
1 ano atrás
Biologia,
1 ano atrás